Beyonds Clicks : Pengaruh ShopeePayLater pada Pembelian Impulsif di E-Commerce, Studi Kasus di Kota Tasikmalaya - Dheri Febiyani Lestari; Setia Rachmanda, Yudi; Kurniawan, Rudi (EKOBIMA, 2023)
The ever-evolving digital world has led to digital transformation in the retail and financial industries, leading to changes in consumer spending trends. Currently, e-commerce offers a variety of payment methods, including the Paylater method, to increase consumer convenience. Shoppe has launched a Paylater feature called ShoppePaylater. Shoppepaylater users can get credit without a long creation process. The aim of this research is to find out how Shoppepaylater influences the impulsive buying behavior of e-commerce users in Tasikmalaya, because Shoppepaylater is thought to make Tasikmalaya people impulsive. As stated by Davis (Nenandha, 2020), differences in the context of use of Shoppepaylater are measured by perceived ease of use, perceived usefulness, intensity of use, and attitudes towards actual use. The indicators of spontaneity, strength, impulse, intensity, excitement, stimulation, and indifference to consequences are used to measure the impulse buying variable proposed by Rook & Fisher (Sari, 2021). This research method is quantitative descriptive analysis and uses data from questionnaires distributed to 186 respondents who met the requirements. From the results of this research, it is known that the impulse buying habits of e-commerce consumers have a 4.2% impact on the ease of use of ShopeePayLater technology in Tasikmalaya. The results of data processing also indicate that consumers in Tasikmalaya have a high level of ShopeePayLater usage and tend to make purchases that do not suit their needs, indicating impulsive behavior in the purchasing process.